Czwarty synod archidiecezji warszawskiej - Gręźlikowski, Janusz (Prawo Kanoniczne, 2009)
The 4th Synod of the Warsaw Archdioceses was debating during the five-year period, between 19th March 1998 and 19th March 2003 when the Warsaw Church had been run by the primate of Poland, cardinal Joseph Glemp. He proposed, summoned and carried out the synod and promulgated its resolutions. The initiative of summoning the synod was connected with the need for overall renewal of the religious and moral life of the Warsaw archdiocese. The synod’s deliberations and its resolutions were to cause the betterment of the organization and functioning of administrative and pastoral apparatus in the archdiocese, to normalize the many issues concerning the church and religious life, as well as to improve the laity and clergy’s religious, social and moral level. To achieve, a wide representation of clergy, catholic laity and monks were engaged. The synodical resolutions with its jurisdictional and pastoral nature are signified by strong setting in the teachings of the Second Vatican Council, the Canon Law, the documents of the Holy See and John Paul II, as well as by the resolutions of the Second Polish Plenary Second and the instructions of the Conference of the Polish Episcopate. At the same time they refer to the tradition of the Warsaw archdiocese and remain fully opened for the “tomorrow” of the Church, evangelizing and pastoral objective. Furthermore they undertake, organize and regulate many difficult pastoral issues. Thus the synodical legislator contributed to the renewal, revival and activation of the church and administrative structures of the archdioceses, so they could serve to various pastoral, church and administrative assignments.